Automatic Image Caption Generation Using CNN, RNN and LSTM - Pophale, SS; Mokate, Praveen; Najan, Sandip; Gajare, Sandesh; Swami, Sanket (International Journal of Computer Sciences and Engineering, 2021)
The paper aims at generating automated captions by learning the contents of the image. At present images are annotated with human intervention and it becomes nearly impossible task for huge commercial databases. The image database is given as input to a deep neural network (Convolutional Neural Network (CNN)) encoder for generating “thought vector” which extracts the features and nuances out of our image and RNN (Recurrent Neural Network) decoder is used to translate the features and objects given by our image to obtain sequential, meaningful description of the image .In this paper we are going to explain the survey about image captioning and our proposed system.